Permian–Triassic highly fractionated I‐type granites in the Baituyingzi Mo–Cu area, southeastern Inner Mongolia, NE China: Petrogenesis and tectonic implications. (7th February 2021) - Sun, Yan; Liu, Jianming; Zeng, Qingdong; Wang, Jingbin; Gu, Xuexiang
Abstract : The Permian–Triassic plutons along the Chifeng‐Bayan Obo Fault, southeastern Inner Mongolia, help to provide important constraints on the craton–orogenic boundary of the North China Craton (NCC) and the eastern Central Asian Orogenic Belt (CAOB) and the regionally coeval Mo–Cu mineralization environment. New LA‐ICP‐MS zircon U–Pb data indicate that two granites from the Baituyingzi Mo–Cu area in Chifeng city were emplaced at ca. 274 Ma and ca. 242 Ma. They have high SiO2 (73.44–77.82 wt%) and Na2 O + K2 O (8.49–10.28 wt%) contents and are high‐K calc‐alkaline, with very high differentiation indexes (DI = 97.1–98.3) and low Zr saturation temperatures of whole rocks (703–738°C). They are also characterized by (La/Yb)N ratios of 4.09–9.30 and enrichments in Rb and Th relative to Nb and Ta, with pronounced negative Eu (Eu/Eu* = 0.14–0.50), Ba, Sr, P, and Ti anomalies. Comparatively, the Permian granite has slightly higher zircon εHf(t) values (+1.7 to +4.6) than those of the Triassic granite (εHf(t) = −3.4 to +0.1) and is less alkaline‐rich. These results, combined with petrographic data, indicate that they are highly fractionated I‐type granites. The granites were likely derived from Mesoproterozoic juvenile crust that had experienced subduction‐related fluid metasomatism, and the resulting magmas then underwent extensive fractional crystallization. In combination with regional geology, we propose that: (a) the granites have tectonic affinity with the CAOB and serve as spatial markers for monitoring the juxtaposition of the NCC and the CAOB, and (b) the studied granites and coeval porphyry deposits likely formed in a syn‐ to post‐collisional setting. Abstract : Ca. 274 Ma and ca. 242 Ma highly fractionated I‐type granites are recognized in the southern XMOB. These intrusions have tectonic affinity with the CAOB and formed in a syn‐ to postcollisional setting related to the closure of the PAO.